Imidazo-pyridine-based zinc(ii) complexes as fluorescent hydrogen sulfide probes. Issue 46 (15th November 2021) - Strianese, Maria; Brenna, Stefano; Attilio Ardizzoia, G.; Guarnieri, Daniela; Lamberti, Marina; D'Auria, Ilaria; Pellecchia, Claudio
Abstract : The use of fluorescent zinc complexes as HS − sensors was explored. TD-DFT calculations suggest trigonal bipyramid compounds as intermediates. Bio-imaging experiments indicated the potential of these compounds in the detection of H2 S in living cells. Abstract : In this work we explore the interaction of HS − with a family of fluorescent zinc complexes. In particular we selected a family of complexes with N, O-bidentate ligands aiming at assessing whether the zinc-chelating ligand plays a role in influencing the reactivity of HS − with the complexes under investigation. Different experiments, performed by diverse spectroscopic techniques, provide evidence that HS − binds the zinc center of all the complexes included in this study. The results highlight the potential of the devised systems to be used as HS − /H2 S fluorescent sensors via a coordinative-based approach. To shed light on the species formed in solution when HS − /H2 S interacts with the title complexes and aiming to rationalize the photophysical properties of the sensing constructs, we performed a computational analysis based on the time dependent density functional theory (TD-DFT). Preliminary bio-imaging experiments were also performed and the results indicate the potential of this class of compounds as probes for the detection of H2 S in living cells.